Studies of the Selective O-Alkylation and Dealkylation of Flavonoids. XIX. A Convenient Method for Synthesizing 3, 5, 6, 7, 8-Pentaoxygenated Flavones - YAMASHITA, Kazuyo; KAWAMURA, Yasuhiko; YAMAMOTO, Hitoshi; HORIE, Tokunaru (Chemical & pharmaceutical bulletin, 1995)
The methoxymethyl ethers of 6-hydroxy-5, 7, 8-trimethoxyflavones, which were derived from 2', 5'-dihydroxy-3', 4', 6'-trimethoxyacetophenone, were oxidized with dimethyldioxirane to give the corresponding 3-hydroxyflavones. Selective O-alkylation and dealkylation of the 3-hydroxyflavones were examined and a convenient method for synthesizing the following ten kinds of 3, 5, 6, 7, 8-pentaoxygenated flavones was established : 3-hydroxy-5, 6, 7, 8-tetramethoxyflavones, 3, 5-dihydroxy-6, 7, 8-trimethoxyflavones, 3, 6-dihydroxy-5, 7, 8-trimethoxyflavones, 3, 5, 6-trihydroxy-7, 8-dimethoxyflavones, 3, 5, 6, 7-tetrahydroxy-8-methoxyflavones, and their 3-methyl ethers. Furthermore, 3, 5, 8-trihydroxy-4', 6, 7-trimethoxyflavone, 3, 8-dihydroxy-4', 5, 6, 7-tetramethoxyflavone, and 5, 8-dihydroxy-3, 6, 7-trimethoxyflavones were similarly synthesized and their spectral properties were examined. Additionally, the proposed structures of three natural flavones were revised.